A Case of Hyperbaric Oxygen as Adjunct to Fasciotomies in Compartment Syndrome, Ischemia-Reperfusion Injury, and Delayed Secondary Infection - Dawnielle C. Endly; Joan V. Eggert (University Library System, University of Pittsburgh, 2013)
Background: Fasciotomies are a therapeutic treatment for compartment syndrome, but they also allow reperfusion to tissues that have been hypoxic. We report a case study of a 52-year-old male with an ischemic leg. Despite prophylactic fasciotomies, ischemia-reperfusion injury resulted in delayed myonecrosis and progressive necrotizing fasciitis.  Results: After two hyperbaric oxygen treatments, edema was markedly reduced and all visible wound tissues were well perfused without evidence of ascending infection, allowing the patient more time for further evaluation. The patient did opt for an above the knee amputation in a non-emergent setting and now successfully utilizes a prosthesis for ambulation. Conclusion: Ischemia-reperfusion injury may result in delayed tissue loss in spite of appropriate fasciotomies. Hyperbaric oxygen may be a useful adjunct therapy even when initiated days after the initial injury.